Contextual Effect of School and Other Determinants of Non Smoking Behavior among High School Students in Bantul, Yogyakarta: A Multilevel Analysis - Roviana Nurda Agustin; Endang Sutisna Sulaeman; Hanung Prasetya (Journal of Health Promotion and Behavior, 2019)
Background: Adolescence is a period of initiation of smoking and not smoking behavior. Non-smoking behavior in adolescents is influenced by factors of knowledge, attitudes, subjective norms, perceptions of behavioral control, intention, parental support, teacher support, peer support, and information media exposure. The purpose of this study was to analyze the contextual influence of schools on non-smoking behavior in adolescents in Bantul Regency, Yogyakarta.Subjects and Method: This was a cross sectional study conducted on 13 high schools and 12 vocational high schools in Bantul Regency, Yogyakarta, from September to October 2019. A sample of 200 male adolescents aged 15-18 years was selected by stratified random sampling. The dependent variable was non-smoking behavior in adolescents. The independent variables were knowledge, attitudes, subjective norms, behavioral control perceptions, intentions, parental support, teacher support, peer support, and information media exposure. The data collections were performed using a questionnaire and analyzed using multilevel multiple logistic regression with Stata 13.Results: Non-smoking behavior in adolescents increases with high adolescent knowledge (b= 3.09; 95% CI= 0.86 to 5.33; p= 0.007), positive attitude (b= 2.92; 95% CI= 0.79 to 5.06; p= 0.007), norm subjective supportive (b= 2.81; 95% CI= 0.72 to 4.92; p= 0.009), perception of strong behavioral control (b= 3.60; 95% CI= 1.22 to 5.99; p = 0.003), non-smoking intention is strong (b= 3.09; 95% CI= 0.92 to 5.27; p= 0.005), strong family support (b= 2.80; 95% CI= 0.76 to 4.85; p= 0.007), strong teacher support (b= 2.98; 95% CI= 0.75 to 5.21; p= 0.009), strong peer support (b= 2.58; 95% CI= 0.04 to 5.13; p= 0.046), and exposed to information media (b= 2.27; 95% CI= 0.45 to 4.09; p= 0.014). There was contextual effect of schools non-smoking behavior (ICC = 20.92%).Conclusion: Non-smoking behavior in adolescents is influenced by knowledge, attitude, subjective norm, perceived behavioral control, intention, parental support, teacher support, peer support, and information media exposure. School has a contextual influence on non-smoking behavior in adolescents.Keywords: smoking, teenage behavior, schoolCorrespondence: Roviana Nurda Agustin. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: roviananurda@gmail.com. Mobile: 085747082310Journal of Health Promotion and Behavior (2019), 4(4): 274-286https://doi.org/10.26911/thejhpb.2019.04.04.04